Micro/nanoscale biosensing in microfluidics: Selection of polymers and microstructures - Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr.; Leow, Pei Ling; Md Eaqub, Ali (AENSI Publications, 2013)
Link to publisher's homepage at http://www.aensiweb.com